On infinite dimensional dissipative stochastic operators - Shahidi, Farruh (2012)
We extend the notion of dissipativity of maps to infinite dimensional simplex. We show that a quadratic stochastic operator is continuous on infinite dimensional simplex. We study linear dissipative maps and the limit behavior of their trajectory.